New habitats of three rare orchid species in the Altai Republic (upper Biya River basin) - Vazhov, Sergei V.; Matsyura, Alex V.; Rusanov, Gennady G.; Vazhov, Victor M.; Shtekhman, Alina I. (Acta Biologica Sibirica, 2022)
Many species of Orchidaceae Juss. are known as beautifully flowering plants, having medicinal, food, decorative, and other qualities. All this draws attention to orchids and promotes their extermination. The expansion of the tourism and recreational development of the Altai Republic and the economic activity of the population aggravate the processes of reduction of rare species of the Orchidaceae Juss. In this sense, the search for new orchid locations is relevant. The purpose of this work is to supplement the database on habitats of rare orchid species in the Altai Republic. Five new habitats of three orchid species were established in the northeast Altai in the basin of the upper Biya River. Cypripedium guttatum Sw. Cypripedium macranthon Sw., and Dactylorhiza fuchsii (Druce) Soo (Orchis fuchsii (Druce), information that is missing in the third edition of the Altai Republic Regional Red Book. Two orchid locations were found in the lower reaches of the Tuloy River valley, a third was found in the lower reaches of the Tondoshka River, the fourth was registered near the Turochak village and the fifth was observed on the left bank of the Biya River near the village Verkh-Biysk. All new habitats were registered in the Turochaksky district of the Altai Republic.